Analysis of the content of software engineers training - Kruglik, V.; Osadchyi, V. (Problems of Engineer-Pedagogical Education, 2018)
The article analyzed the curricula of training in the field of knowledge 12 "Information Technology" educational institutions of Ukraine. On this basis, were identified and grouped into blocks of disciplines (informatics, mathematics, programming, electronics, project management, linguistic, practical). The list of subjects is not sufficiently illuminated professional component. In order to select appropriate content of training curricula are considered leading foreign universities. Based on the analysis of domestic and foreign training programs were selected disciplines that make up the core training of future engineers and programmers. To display the logical connections between disciplines based network diagram normative part of the curriculum. In researched the professional competence, which are formed during the study subjects that make up the core training of future engineers-programmers are determinate.